1981
DOI: 10.1073/pnas.78.8.4867
|View full text |Cite
|
Sign up to set email alerts
|

Primary structure and evolution of rat growth hormone gene.

Abstract: The rat growth hormone gene was isolated on a cloned 11.4-kilobase EcoRI-generated DNA fragment from a bacteriophage "library" of chromosomal DNA. The structural gene sequence, -2. 1 kilobases long, was identified by hybridization to the corresponding cloned rat growth hormone cDNA and shown to contain four intervening sequences. The complete primary structure of the gene and the 5'-and 3'-flanking regions was determined. The mosaic structure of exons and introns can be related to the different biological acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
101
1

Year Published

1983
1983
1999
1999

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 249 publications
(105 citation statements)
references
References 34 publications
(32 reference statements)
3
101
1
Order By: Relevance
“…An examination of the Pol III promoter sequences revealed that the rGH TR, but not the type 2 DNA, contains a significant A58+G change at an invariant position in the B box promoter region. Surprisingly, we found this change to be conserved in all eleven TR elements sequenced so far (3,7,(9)(10)(11)(12)(13)(14)(15). It could be argued that this "nonpermissive" change of the invariant A58 to a G is responsible for the lack of TR Pol III activity in vitro.…”
Section: Cell-free Transcriptionmentioning
confidence: 83%
See 3 more Smart Citations
“…An examination of the Pol III promoter sequences revealed that the rGH TR, but not the type 2 DNA, contains a significant A58+G change at an invariant position in the B box promoter region. Surprisingly, we found this change to be conserved in all eleven TR elements sequenced so far (3,7,(9)(10)(11)(12)(13)(14)(15). It could be argued that this "nonpermissive" change of the invariant A58 to a G is responsible for the lack of TR Pol III activity in vitro.…”
Section: Cell-free Transcriptionmentioning
confidence: 83%
“…1). Another single TR is found 300-500 bp beyond the rGH gene polyadenylation signal ( The putative 'identifier" sequence is equivalent to the rGH TR sequences and therefore is a member of the TR family (3,(7)(8)(9)(10)(11)(12)(13)(14)(15).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Genes compared are from rat growth hormone (rGH), mouse renin genes (Renl and Ren2), human growth hormone (hGH), angiotensinogen and the cu-subunit of mouse nerve growth factor ((uNGF). The positions relative to the principal transcriptional start point have been indicated the rGH (positions -248 to -257 relative to the transcription start point [16]), and in the two mouse renin genes (positions -455 to -464 for Ren 1; -666 to -675 for Ren2 [17]). The second conserved element which is the dodecanucleotide GAAAACAGGTAG is found in the three genes with only one mismatch (the C is replaced by a G in the two renin genes).…”
Section: Discussionmentioning
confidence: 99%